Channelopathy of Dravet Syndrome and Potential Neuroprotective Effects of Cannabidiol. (11th October 2021) - Xu, Changqing; Zhang, Yumin; Gozal, David; Carney, Paul
Dravet syndrome (DS) is a channelopathy, neurodevelopmental, epileptic encephalopathy characterized by seizures, developmental delay, and cognitive impairment that includes susceptibility to thermally induced seizures, spontaneous seizures, ataxia, circadian rhythm and sleep disorders, autistic-like behaviors, and premature death. More than 80% of DS cases are linked to mutations in genes which encode voltage-gated sodium channel subunits, SCN1A and SCN1B, which encode the Nav1.1α subunit and Nav1.1β1 subunit, respectively. There are other gene mutations encoding potassium, calcium, and hyperpolarization-activated cyclic nucleotide-gated (HCN) channels related to DS. One-third of patients have pharmacoresistance epilepsy. DS is unresponsive to standard therapy. Cannabidiol (CBD), a non-psychoactive phytocannabinoid present in Cannabis, has been introduced for treating DS because of its anticonvulsant properties in animal models and humans, especially in pharmacoresistant patients. However, the etiological channelopathiological mechanism of DS and action mechanism of CBD on the channels are unclear. In this review, we summarize evidence of the direct and indirect action mechanism of sodium, potassium, calcium, and HCN channels in DS, especially sodium subunits. Some channels' loss-of-function or gain-of-function in inhibitory or excitatory neurons determine the balance of excitatory and inhibitory are associated with DS. A great variety of mechanisms of CBD anticonvulsant effects are focused on modulating these channels, especially sodium, calcium, and potassium channels, which will shed light on ionic channelopathy of DS and the precise molecular treatment of DS in the future.